(untitled) (Jornal Memorial da Medicina, 2020)
The pathophysiology of Covid-19 has a cytokine storm, causing exacerbation of inflammatory lesions, mainly of the lungs and vascular endothelium. The mechanism of entry into the human cell uses the Angiotensin-Converting Enzyme 2 as a cell surface receptor. Among the most at-risk groups are pregnant women, due to the physiological, anatomical and immunological changes of the gestational cycle, causing susceptibility to infections. In addition, there are uncertainties about safe breastfeeding and possible vertical transmission. This group, which has a continuous obstetric follow-up, within pandemic circumstances, needed to minimize the risk of exposure in medical settings, using care through telehealth, as a helper. It was possible to replace some face-to-face visits to the clinic, when possible, by virtual ones, minimizing risks to exposure and providing a vehicle for direct communication with the doctor, which, in a way, offers pregnant women more peace of mind, essential to avoid possible complications by psychological stress that can generate inflammatory responses for mother and fetus, causing possible neuropsychiatric consequences. The objective of this narrative review study was to present an update of the data on the disease, as well as a change in management of the pregnant population. Despite being of great importance, virtual assistance does not replace face-to-face, and to get the most out of this new approach, there is a set of guidelines that can help health professionals. It is also important to warn of: changes in hospital management; reconciling ultrasound consultations with medical appointments, reducing the number of pregnant women leavings; telephone tracking of patients’ symptoms before face-to-face attendance; and testing recommendations for covid-19, before entering hospitals.